Rombert Stapel. Medieval Authorship and Cultural Exchange in the Late Fifteenth Century. The Utrecht Chronicle of the Teutonic Order. Abingdon‒NewYork: Routledge 2021. 462 pp. ISBN: 978-0-429-35312-3. - Päsler, Ralf G. (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)